THE EFFECT OF DISCIPLINE, MOTIVATION AND WORK ENVIRONMENT ON TEACHER PERFORMANCE AT SMPN 13, 17 AND 21 DEPOK - Hamsinah, Hamsinah (LPPM STIE Muhammadiah Bandung, 2020)
The purpose of this research is to analyze the various questions stated in the problem formulation. the design used is a descriptive design and a study of the relationship between variables (causal design) is also carried out which is useful for measuring the relationship between research variables or for analyzing how one variable influences other variables. In this study, the data were collected ex post facto, in other words, the researcher relied on the respondents' perceptions to explain their experiences and then analyzed them according to descriptive and causal designs. The data collection technique in this study used a survey method, with a closed questionnaire, in which the respondent chose one of the answers provided, with alternative answers consisting of an interval of 1 – 5. the probability value of Sig 0.000 <0.05 then Ho3 is rejected, Ha3 is accepted, thus the hypothesis stipulates that the Work Environment (X3) has a positive and significant effect on Teacher Performance (Y) at SMPN 13, SMPN 17, SMPN 21 Depok